2022
DOI: 10.7717/peerj.14198
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and meristic diversity of the species Androctonus crassicauda (Olivier, 1807) (Scorpiones: Buthidae) in Saudi Arabia

Abstract: Intraspecific molecular and morphological variations among geographically isolated populations are useful for understanding the evolutionary processes, which is considered early stage of allopatric speciation. Also, the knowledge of the regional variation of scorpion venom composition is needed to improve antivenom therapeutic management. Androctonus crassicauda (Olivier, 1807) is the most common and medically important species in Arabia and the Middle East. Therefore, this study aimed to investigate the geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The status of Androctonus crassicauda in Kuwait deserves a closer examination. Alqahtani et al (2022) showed that the populations of this species in Saudi Arabia have several distinct forms, and those from the North Arabian Desert are distinct from those of the Central Arabian Desert and other population in the south and western Saudi Arabia, suggesting the existence of different species within the A. crassicauda complex. The Kuwaiti Androctonus populations should be compared with A. sumericus.…”
Section: Discussionmentioning
confidence: 92%
“…The status of Androctonus crassicauda in Kuwait deserves a closer examination. Alqahtani et al (2022) showed that the populations of this species in Saudi Arabia have several distinct forms, and those from the North Arabian Desert are distinct from those of the Central Arabian Desert and other population in the south and western Saudi Arabia, suggesting the existence of different species within the A. crassicauda complex. The Kuwaiti Androctonus populations should be compared with A. sumericus.…”
Section: Discussionmentioning
confidence: 92%
“…nov., and this record probably was the new species. In molecular and morphometrical investigations, Alqahtani et al (2022a , b , c ) referred to the existence of three distinct clusters of A. crassicauda populations collected from different ecogeographical regions in Saudi Arabia, and the Arabian clade is placed as a basal clade to Turkey and Iran sequences.…”
Section: Discussionmentioning
confidence: 99%
“…The genus has 36 valid species ( Rein 2023 ), of which most species are known to deliver severe stings. Androctonus is also very taxonomically confused due to great intraspecific morphological and molecular variation (Ben Ali et al 2000; Lourenço 2005 ; Lourenço and Qi 2006 , 2007 ; Lourenço 2008 ; Othmen et al 2009 ; Alqahtani et al 2022a , b ). As already shown by Hendrixson (2006) and Alqahtani et al (2019) , several Androctonus species are widely distributed in Saudi Arabia, where they inhabit diverse habitats.…”
Section: Introductionmentioning
confidence: 99%